A flower-like MoS2-induced Fe2O3 / Fe2(MoO4)3 nanocomposite material and its preparation method and application

The preparation of Fe2O3/Fe2(MoO4) 3-nano composite material was solved by hydrothermal method and microwave-assisted technology, and the problem of poor gas sensitivity performance of MoS2 composite material was solved, achieving high selectivity and stability response to ethanol gas.

CN117607219BActive Publication Date: 2025-04-04ZHONGYUAN ENGINEERING COLLEGE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311613948.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2025-04-04
Estimated Expiration
2043-11-29

AI Technical Summary

Technical Problem

The existing MoS2 composite materials have problems such as too long response/recovery time, high operating temperature and poor selectivity in terms of gas-sensitive performance, which limits their application in the field of gas-sensitive sensors.

Method used

MoS2 nanomaterial was prepared by hydrothermal method, and Fe(OH)3/MoS2 nanocomposite was synthesized under microwave-assisted conditions, and then calcined in the air to form Fe2O3/Fe2(MoO4)3 nanocomposite, improving its gas-sensitive properties.

Benefits of technology

The obtained Fe2O3/Fe2(MoO4) 3-nano composite material has good selectivity and stability response to ethanol gas, solving the problems of excessive detection temperature and poor stability of gas-sensitive sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117607219B_ABST
    Figure CN117607219B_ABST
Patent Text Reader

Abstract

The present invention proposes a Fe2O3 / Fe2(MoO4)3 nanocomposite material induced by a flower-shaped MoS2 substrate, and a preparation method and application thereof, which belongs to the technical field of material synthesis. The preparation method of the Fe2O3 / Fe2(MoO4)3 nanocomposite material of the present invention comprises the following steps: dissolving and mixing a molybdenum source and a sulfur source in a solvent I, adjusting the pH, and obtaining molybdenum disulfide through a hydrothermal reaction; dispersing and dissolving molybdenum disulfide and an iron source in a solvent II, adding a precipitant, reacting under microwave-assisted conditions, washing and drying the product; calcining the dried product, and obtaining the Fe2O3 / Fe2(MoO4)3 nanocomposite material by a two-step method. The Fe2O3 / Fe2(MoO4)3 nanocomposite material obtained by the present invention has good selectivity and stability response to ethanol gas, which is of great significance for effectively solving the problems of excessively high detection temperature and poor stability of gas sensors existing in previous gas-sensitive detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material synthesis, and in particular relates to a flower-shaped MoS2-induced Fe2O3 / Fe2(MoO4)3 nanocomposite material and a preparation method and application thereof. Background Art

[0002] With the improvement of industrialization and living standards, the issue of air quality has attracted more and more attention. In terms of indoor air quality, it has been found that common organic volatile compounds in a large number of interior decoration and decorative materials, including methanol, ethanol, benzene, toluene, formaldehyde and acetone, have serious pollution to indoor air. For example, formaldehyde and xylene are widely used in the synthesis of polyester and as solvents in printing, rubber, leather and other industries as well as household products; aerosol paints and lacquers, as well as common cosmetics for women, such as nail polish and mascara, all contain certain organic volatile substances. The toxic and harmful gases formed by the volatilization of organic matter cannot be ignored. Especially for the human respiratory system, central nervous system, and eyes and skin exposed to the air. The National Institute for Occupational Safety and Health recommends that for organic volatile liquids such as xylene, the long-term and short-term exposure limits are 100 and 150 ppm respectively. It can be seen that the detection of low-concentration organic volatile liquids is very necessary.

[0003] The identification and early warning of specific toxic and harmful gases by gas sensors play a vital role in preventing pollution, controlling pollution and reducing the occurrence of public safety incidents. They have been widely used in daily life, medical diagnosis, agricultural production and industrial safety. It is crucial to find an effective and sensitive method to monitor air pollution. At present, a variety of gas sensor monitors have been successfully produced and applied in various fields. Among various types of gas sensors, gas sensors based on metal oxide semiconductors have become a hot research object due to their environmental protection, portability and low cost. Studies have shown that gas sensors prepared with SnO2, TiO2, ZnO, Fe2O3 and conductive polymers as materials have the advantages of high sensitivity, low power consumption, low cost, short response recovery time, etc., and can well realize the detection of harmful gases. However, they still have disadvantages, such as poor selectivity, high test working temperature, high energy consumption and short life. The sensitivity is low at room temperature, which limits its development and application. Therefore, gas sensors with high sensitivity, low test temperature, good selectivity, short response recovery time and good stability have become the current research direction of gas sensors.

[0004] At present, many researchers have improved the performance of materials by preparing composite materials based on two-dimensional MoS2. Among them, composite materials such as SnO2 / MoS2, MoS2 / Co3O4, MoS2 / ZnO and MoS2 / TiO2 have been widely studied, and the gas-sensing performance of MoS2 modified by composite means has been improved to a certain extent. In many studies on MoS2 composite materials and two-dimensional MoS2, researchers usually use hydrothermal method to prepare MoS2 composite materials and CVD method to prepare a few layers of MoS2 thin film.

[0005] Composite with a second phase metal oxide is a common composite method to improve the gas sensing properties of molybdenum disulfide. Akhtar et al. (Akhtar A., ​​Chu XF, Liang SM, et al. Enhanced formaldehyde sensing properties of MoS2-Zn2SnO4 nanocomposites synthesized via hydrothermal method [J]. Inorganic Chemistry Communications, 2021.) used a hydrothermal method to synthesize MoS2-Zn2SnO4 nanocomposites. The increased oxygen content and surface area of ​​MZSO-5 jointly improved the formaldehyde adsorption capacity. Studies have shown that the response of the MSZO-5-based sensor to a formaldehyde gas concentration of 100 ppm at a temperature of 110°C is 22. Kumar et al. (Kumar RR, Murugesan T. Ultrasensitive and light-activated NO2 gas sensorbased on networked MoS2 / ZnO nanohybrid with adsorption / desorption kinetics study[J]. Applied Surface Science, 2021.) used MoS2 / ZnO nanocomposite to prepare a high-performance NO2 gas sensor at room temperature. The nanocomposite was prepared by dripping MoS2 nanosheet solution on zinc oxide nanorods. The uniform network distribution of MoS2 nanosheets on the nanorods was confirmed by various characterization techniques. Under ultraviolet irradiation, the nanocomposite gas sensor showed strong sensitivity to NO2 at concentrations of 5ppb and 500ppb. Singh et al. (Singh S., Raj S., Sharma S. Ethanol sensing using MoS2 / TiO2 composite prepared via hydro thermal method[J]. Materials Today: Proceedings, 2020.) prepared MoS2 / TiO2 composite by hydrothermal method. The ethanol vapor detection was successfully realized at 350°C, and the MoS2 / TiO2 composite material had a high sensitivity to ethanol at a concentration of 100 ppm. The gas-sensing properties of the composite material were tested in NO2, NH3, H2S, methanol and ethanol, and it was concluded that the composite material had excellent selectivity for ethanol.Wang et al. (Wang WX, Zhen YH, et al. SnO2 nanoparticles-modified 3D-multilayer MoS2 nanosheets for ammonia gas sensing at room temperature [J]. Sensors and Actuators B: Chemical, 2020.) successfully prepared a sheet-like SnO2 / MoS2 nanoheterostructure by a two-step hydrothermal method. The composite material has a sensing composite structure of a support layer / sensitive point. The nanocomposite material showed good responsiveness to NH3 at a concentration of 200ppm, and achieved rapid recognition of ammonia at a concentration of 50ppm at room temperature with good repeatability. The response time and recovery time were 23s and 1.6s, respectively. The study found that the unique flower-like thin layer assembly structure of two-dimensional MoS2 promoted the carrier charge transfer process and enhanced the reaction between SnO2 / MoS2 and NH3, which is the main reason for improving its gas sensing performance.

[0006] In summary, by analyzing and summarizing a large number of research reports on the preparation and gas sensing properties of MoS2, it is found that the hydrothermal method is widely used in the research of MoS2 composites, and the MoS2 composites prepared by the hydrothermal method have been improved to a certain extent in terms of gas sensing properties. However, there are still some problems, such as: the response / recovery time of MoS2 composites is too long, the working temperature of gas sensitive materials is high, and the selectivity is poor, which restricts the application of two-dimensional MoS2 nanomaterials in the field of gas sensors. Summary of the invention

[0007] In order to solve the technical problem that MoS2 composite materials have poor gas-sensing properties, the present invention proposes a flower-shaped MoS2 substrate-induced Fe2O3 / Fe2(MoO4)3 nanocomposite material, a preparation method and an application thereof. The prepared Fe2O3 / Fe2(MoO4)3 nanocomposite material shows good gas-sensitive response characteristics to ethanol.

[0008] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0009] A method for preparing a Fe2O3 / Fe2(MoO4)3 nanocomposite material comprises the following steps:

[0010] (1) dissolving and mixing a molybdenum source and a sulfur source in a solvent I, adjusting the pH, and obtaining molybdenum disulfide through a hydrothermal reaction;

[0011] (2) dispersing and dissolving molybdenum disulfide and an iron source in solvent II, adding a precipitant, reacting under microwave-assisted conditions, and washing and drying the product;

[0012] (3) The dried product is calcined in air to obtain a Fe2O3 / Fe2(MoO4)3 nanocomposite material.

[0013] The molybdenum source is sodium molybdate; the sulfur source is thiourea; and the solvent I is water or ethanol.

[0014] The molar ratio of the molybdenum source to the sulfur source is 1:(3-5); the concentration of the molybdenum source in solvent I is 0.01-0.1 mmol / ml.

[0015] The reagent used for adjusting the pH is concentrated hydrochloric acid, and the pH is adjusted to 1.5-2.5; the temperature of the hydrothermal reaction is 160° C.-230° C., and the reaction time is 12h-24h.

[0016] The iron source is ferric nitrate; the solvent II is water or ethanol; and the precipitant is urea or ammonia water.

[0017] In the step (2), the ratio of molybdenum atoms to iron atoms in molybdenum disulfide and iron source is (8-3):(2-7); the molar ratio of the iron source to the precipitant is 1:(3-6), and the concentration of molybdenum disulfide in solvent II is 0.05-0.2 mmol / ml.

[0018] The microwave-assisted conditions are: reaction temperature of 80°C-110°C, microwave power of 100-1000W, and time of 1-20min.

[0019] The calcination temperature is 300-700° C. and the calcination time is 0.5-5 h.

[0020] The Fe2O3 / Fe2(MoO4)3 nanocomposite material is prepared by the above method.

[0021] A flower-like MoS2-induced Fe2O3 / Fe2(MoO4)3 nanocomposite material is used in gas concentration detection, preferably for the detection of ethanol gas.

[0022] The invention has the beneficial effects of preparing MoS2 nanomaterials by hydrothermal method, synthesizing Fe(OH)3 / MoS2 nanocomposite materials by microwave-assisted method, and calcining in air to generate Fe2O3 / Fe2(MoO4)3 nanocomposite materials. The Fe2O3 / Fe2(MoO4)3 nanocomposite materials have a large specific surface area, which means that there are more surfaces available for gas adsorption and reaction per unit mass. This helps to improve the interaction between gas and material, thereby improving gas sensing performance. Calcination in air can solve the disadvantage of poor gas sensitivity of MoS2. After calcination in air, MoS2 reacts with oxygen in the air at high temperature to generate MoO3 and release heat. At the same time, Fe(OH)3 particles uniformly attached to the surface of MoS2 petals absorb heat and decompose to generate Fe2O3 under the action of microwaves. Since the two reactions proceed simultaneously, Fe2(MoO4)3 composed of MoO3 and Fe2O3 with a large number of heterojunction interfaces is generated under the synergistic promotion of each other, while a small amount of Fe(OH)3 far from the surface of MoS2 petals reacts in situ to generate Fe2O3 uniformly distributed on the Fe2(MoO4)3 substrate; in addition, the SO2 and H2O gases released during the reaction create a large number of pores, which are conducive to the improvement of gas sensing performance. In summary, the obtained Fe2O3 / Fe2(MoO4)3 nanocomposite material has good selectivity and stability response to ethanol gas, which is of great significance for effectively solving the problems of too high detection temperature and poor stability of gas sensors in previous gas sensing detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 The following are electron microscope images of MoS2, where (a) and (b) are MoS2 prepared in Example 1; (c) and (d) are MoS2 prepared in Example 2.

[0025] Figure 2 SEM images of the Fe2O3 / Fe2(MoO4)3 nanocomposite material prepared in Example 4; in the figure, (a) is a low-magnification SEM image; (b) is a high-magnification SEM image.

[0026] Figure 3 XRD pattern of Fe2O3 / Fe2(MoO4)3 nanocomposite material prepared in Example 4.

[0027] Figure 4 The gas-sensitive response-time dynamic change curve of the Fe2O3 / Fe2(MoO4)3 nanocomposite material prepared in Example 4 to ethanol.

[0028] Figure 5 The sensitivity and temperature relationship diagram of the Fe2O3 / Fe2(MoO4)3 nanocomposite material prepared in Example 4 to ethanol gas at different concentrations.

[0029] Figure 6 This is a response recovery time diagram of the Fe2O3 / Fe2(MoO4)3 nanocomposite material prepared in Example 4 at various temperatures.

[0030] Figure 7 The selectivity of the Fe2O3 / Fe2(MoO4)3 nanocomposite material prepared in Example 4 for different organic volatile liquids. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] A flower-shaped MoS2-induced Fe2O3 / Fe2(MoO4)3 nanocomposite material, the preparation method of which comprises the following steps:

[0034] (1) Dissolve 1.6 mmol of sodium molybdate (Na2MoO4; 98%) and 8 mmol of thiourea (H2NCS-NH2; 99%) in 40 mL of deionized water; continue stirring for 10 min to completely dissolve the sodium molybdate and thiourea; adjust the pH value to 2 with concentrated hydrochloric acid;

[0035] (2) The prepared solution was transferred to a reactor containing 50 ml of solvent; the reaction temperature was controlled to be 210°C and the reaction time was 12 hours; after the reaction was completed, the solution was taken out and naturally cooled to room temperature, centrifuged at 4000 rpm with distilled water for 3-5 minutes, washed with water four times by centrifugation, and then washed once with alcohol by centrifugation to obtain MoS2.

[0036] (3) The weighed MoS2 prepared by the hydrothermal method was placed in a drying oven at 60°C and dried for 12 hours before being taken out.

[0037] (4) Weigh 1.28 g of dried molybdenum disulfide and 0.808 g of ferric nitrate nonahydrate into a 100 ml conical flask, add 50 ml of deionized water, seal with plastic wrap, add a stirrer, and stir on a magnetic stirrer for 40 min; add 3.36 g of 25 wt % ammonia water dropwise, and continue stirring on the magnetic stirrer for 20 min;

[0038] (5) The stirred solution was placed in a microwave reaction box and reacted at 95°C and 400W for 3 minutes; the solution after the reaction was cooled naturally, and then washed with distilled water by centrifugation at 4000 rpm for 4 times, and then washed once with anhydrous ethanol, and then the resultant was placed in a drying oven at 60°C and dried for 12 hours;

[0039] (6) The dried product was placed in a crucible and calcined at 550°C in an air atmosphere for 2.5 h to obtain a Fe2O3 / Fe2(MoO4)3 nanocomposite material.

[0040] Example 2

[0041] A flower-shaped MoS2-induced Fe2O3 / Fe2(MoO4)3 nanocomposite material, the preparation method of which comprises the following steps:

[0042] (1) Dissolve 1.6 mmol of sodium molybdate (Na2MoO4; 98%) and 8 mmol of thiourea (H2NCS-NH2; 99%) in 40 mL of deionized water; continue stirring for 10 min to completely dissolve the sodium molybdate and thiourea; adjust the pH value to 2 with concentrated hydrochloric acid;

[0043] (2) The prepared solution was transferred to a reactor containing 50 ml of solvent; the reaction temperature was controlled to be 210°C and the reaction time was 12 hours; after the reaction was completed, the solution was taken out and naturally cooled to room temperature, centrifuged at 4000 rpm with distilled water for 3-5 minutes, washed with water four times by centrifugation, and then washed once with alcohol by centrifugation to obtain MoS2.

[0044] (3) The weighed MoS2 prepared by the hydrothermal method was placed in a drying oven at 60°C and dried for 12 hours before being taken out.

[0045] (4) Weigh 1.12 g of dried molybdenum disulfide and 1.212 g of ferric nitrate nonahydrate into a 100 ml conical flask, add 50 ml of deionized water, seal with plastic wrap, add a stirrer, and stir on a magnetic stirrer for 40 min; add 2.94 g of 25 wt % ammonia water dropwise, and continue stirring on the magnetic stirrer for 20 min;

[0046] (5) The stirred solution was placed in a microwave reaction box and reacted at 95°C and 400W for 3 minutes; the solution after the reaction was cooled naturally, and then washed with distilled water by centrifugation at 4000 rpm for 4 times, and then washed once with anhydrous ethanol, and then the resultant was placed in a drying oven at 60°C and dried for 12 hours;

[0047] (6) The dried product was placed in a crucible and calcined at 550°C in an air atmosphere for 2.5 h to obtain a Fe2O3 / Fe2(MoO4)3 nanocomposite material.

[0048] Example 3

[0049] A flower-shaped MoS2-induced Fe2O3 / Fe2(MoO4)3 nanocomposite material, the preparation method of which comprises the following steps:

[0050] (1) Dissolve 1.6 mmol of sodium molybdate (Na2MoO4; 98%) and 8 mmol of thiourea (H2NCS-NH2; 99%) in 40 mL of deionized water; continue stirring for 10 min to completely dissolve the sodium molybdate and thiourea; adjust the pH value to 2 with concentrated hydrochloric acid;

[0051] (2) The prepared solution was transferred to a reactor containing 50 ml of solvent; the reaction temperature was controlled to be 210°C and the reaction time was 12 hours; after the reaction was completed, the solution was taken out and naturally cooled to room temperature, centrifuged at 4000 rpm with distilled water for 3-5 minutes, washed with water four times by centrifugation, and then washed once with alcohol by centrifugation to obtain MoS2.

[0052] (3) The weighed MoS2 prepared by the hydrothermal method was placed in a drying oven at 60°C and dried for 12 hours before being taken out.

[0053] (4) Weigh 0.96 g of dried molybdenum disulfide and 1.616 g of ferric nitrate nonahydrate into a 100 ml conical flask, add 50 ml of deionized water, seal with plastic wrap, add a stirrer, and stir on a magnetic stirrer for 40 min; add 2.52 g of 25 wt % ammonia water dropwise, and continue stirring on the magnetic stirrer for 20 min;

[0054] (5) The stirred solution was placed in a microwave reaction box and reacted at 95°C and 400W for 3 minutes; the solution after the reaction was cooled naturally, and then washed with distilled water by centrifugation at 4000 rpm for 4 times, and then washed once with anhydrous ethanol, and then the resultant was placed in a drying oven at 60°C and dried for 12 hours;

[0055] (6) The dried product was placed in a crucible and calcined at 550°C in an air atmosphere for 2.5 h to obtain a Fe2O3 / Fe2(MoO4)3 nanocomposite material.

[0056] Example 4

[0057] A flower-shaped MoS2-induced Fe2O3 / Fe2(MoO4)3 nanocomposite material, the preparation method of which comprises the following steps:

[0058] (1) Dissolve 1.6 mmol of sodium molybdate (Na2MoO4; 98%) and 8 mmol of thiourea (H2NCS-NH2; 99%) in 40 mL of deionized water; continue stirring for 10 min to completely dissolve the sodium molybdate and thiourea; adjust the pH value to 2 with concentrated hydrochloric acid;

[0059] (2) The prepared solution was transferred to a reactor containing 50 ml of solvent; the reaction temperature was controlled to be 210°C and the reaction time was 12 hours; after the reaction was completed, the solution was taken out and naturally cooled to room temperature, centrifuged at 4000 rpm with distilled water for 3-5 minutes, washed with water four times by centrifugation, and then washed once with alcohol by centrifugation to obtain MoS2.

[0060] (3) The weighed MoS2 prepared by the hydrothermal method was placed in a drying oven at 60°C and dried for 12 hours before being taken out.

[0061] (4) Weigh 0.8 g of dried molybdenum disulfide and 2.02 g of ferric nitrate nonahydrate into a 100 ml conical flask, add 50 ml of deionized water, seal with plastic wrap, add a stirrer, and stir on a magnetic stirrer for 40 min; add 2.1 g of 25 wt % ammonia water dropwise, and continue stirring on the magnetic stirrer for 20 min;

[0062] (5) The stirred solution was placed in a microwave reaction box and reacted at 95°C and 400W for 3 minutes; the solution after the reaction was cooled naturally, and then washed with distilled water by centrifugation at 4000 rpm for 4 times, and then washed once with anhydrous ethanol, and then the resultant was placed in a drying oven at 60°C and dried for 12 hours;

[0063] (6) The dried product was placed in a crucible and calcined at 550°C in an air atmosphere for 2.5 h to obtain a Fe2O3 / Fe2(MoO4)3 nanocomposite material.

[0064] Example 5

[0065] A flower-shaped MoS2-induced Fe2O3 / Fe2(MoO4)3 nanocomposite material, the preparation method of which comprises the following steps:

[0066] (1) Dissolve 1.6 mmol of sodium molybdate (Na2MoO4; 98%) and 8 mmol of thiourea (H2NCS-NH2; 99%) in 40 mL of deionized water; continue stirring for 10 min to completely dissolve the sodium molybdate and thiourea; adjust the pH value to 2 with concentrated hydrochloric acid;

[0067] (2) The prepared solution was transferred to a reactor containing 50 ml of solvent; the reaction temperature was controlled to be 210°C and the reaction time was 12 hours; after the reaction was completed, the solution was taken out and naturally cooled to room temperature, centrifuged at 4000 rpm with distilled water for 3-5 minutes, washed with water four times by centrifugation, and then washed once with alcohol by centrifugation to obtain MoS2.

[0068] (3) The weighed MoS2 prepared by the hydrothermal method was placed in a drying oven at 60°C and dried for 12 hours before being taken out.

[0069] (4) Weigh 0.64 g of dried molybdenum disulfide and 2.424 g of ferric nitrate nonahydrate into a 100 ml conical flask, add 50 ml of deionized water, seal with plastic wrap, add a stirrer, and stir on a magnetic stirrer for 40 min; add 1.68 g of 25 wt % ammonia water dropwise, and continue stirring on the magnetic stirrer for 20 min;

[0070] (5) The stirred solution was placed in a microwave reaction box and reacted at 95°C and 400W for 3 minutes; the solution after the reaction was cooled naturally, and then washed with distilled water by centrifugation at 4000 rpm for 4 times, and then washed once with anhydrous ethanol, and then the resultant was placed in a drying oven at 60°C and dried for 12 hours;

[0071] (6) The dried product was placed in a crucible and calcined at 550°C in an air atmosphere for 2.5 h to obtain a Fe2O3 / Fe2(MoO4)3 nanocomposite material.

[0072] Example 6

[0073] A flower-shaped MoS2-induced Fe2O3 / Fe2(MoO4)3 nanocomposite material, the preparation method of which comprises the following steps:

[0074] (1) Dissolve 1.6 mmol of sodium molybdate (Na2MoO4; 98%) and 8 mmol of thiourea (H2NCS-NH2; 99%) in 40 mL of deionized water; continue stirring for 10 min to completely dissolve the sodium molybdate and thiourea; adjust the pH value to 2 with concentrated hydrochloric acid;

[0075] (2) The prepared solution was transferred to a reactor containing 50 ml of solvent; the reaction temperature was controlled to be 210°C and the reaction time was 12 hours; after the reaction was completed, the solution was taken out and naturally cooled to room temperature, centrifuged at 4000 rpm with distilled water for 3-5 minutes, washed with water four times by centrifugation, and then washed once with alcohol by centrifugation to obtain MoS2.

[0076] (3) The weighed MoS2 prepared by the hydrothermal method was placed in a drying oven at 60°C and dried for 12 hours before being taken out.

[0077] (4) Weigh 0.48 g of dried molybdenum disulfide and 2.828 g of ferric nitrate nonahydrate into a 100 ml conical flask, add 50 ml of deionized water, seal with plastic wrap, add a stirrer, and stir on a magnetic stirrer for 40 min; add 1.26 g of 25 wt % ammonia water dropwise, and continue stirring on the magnetic stirrer for 20 min;

[0078] (5) The stirred solution was placed in a microwave reaction box and reacted at 95°C and 400W for 3 minutes; the solution after the reaction was cooled naturally, and then washed with distilled water by centrifugation at 4000 rpm for 4 times, and then washed once with anhydrous ethanol, and then the resultant was placed in a drying oven at 60°C and dried for 12 hours;

[0079] (6) The dried product was placed in a crucible and calcined at 550°C in an air atmosphere for 2.5 h to obtain a Fe2O3 / Fe2(MoO4)3 nanocomposite material.

[0080] Example 7

[0081] A flower-shaped MoS2-induced Fe2O3 / Fe2(MoO4)3 nanocomposite material, the preparation method of which comprises the following steps:

[0082] (1) Dissolve 1.6 mmol of sodium molybdate (Na2MoO4; 98%) and 6.4 mmol of thiourea (H2NCS-NH2; 99%) in 16 mL of deionized water; continue stirring for 10 min to completely dissolve the sodium molybdate and thiourea; adjust the pH value to 2.5 with concentrated hydrochloric acid;

[0083] (2) Transfer the prepared solution to a reactor containing 50 ml of solvent; control the reaction temperature to 160°C and the reaction time to 24 hours; after the reaction is completed, take it out and naturally cool it to room temperature, centrifuge it with distilled water at a speed of 4000 rpm for 3-5 minutes, wash it with water centrifugation 4 times, and then centrifuge it with alcohol to obtain MoS2.

[0084] (3) The weighed MoS2 prepared by the hydrothermal method was placed in a drying oven at 60°C and dried for 12 hours before being taken out.

[0085] (4) Weigh 0.48 g of dried molybdenum disulfide and 2.828 g of ferric nitrate nonahydrate into a 100 ml conical flask, add 25 ml of deionized water, seal with plastic wrap, add a stirrer, and stir on a magnetic stirrer for 40 min; add 2.52 g of 25 wt % ammonia water dropwise, and continue stirring on the magnetic stirrer for 20 min;

[0086] (5) The stirred solution was placed in a microwave reaction box and reacted at 110°C and 100W for 20 minutes; the solution after the reaction was cooled naturally, and then washed with distilled water by centrifugation at 4000 rpm for 4 times, and then washed once with anhydrous ethanol, and then the resultant was placed in a drying oven at 60°C and dried for 12 hours;

[0087] (6) The dried product was placed in a crucible and calcined at 300°C in an air atmosphere for 5 h to obtain a Fe2O3 / Fe2(MoO4)3 nanocomposite material.

[0088] Example 8

[0089] A flower-shaped MoS2-induced Fe2O3 / Fe2(MoO4)3 nanocomposite material, the preparation method of which comprises the following steps:

[0090] (1) Dissolve 1.6 mmol of sodium molybdate (Na2MoO4; 98%) and 4.8 mmol of thiourea (H2NCS-NH2; 99%) in 160 mL of deionized water; continue stirring for 10 min to completely dissolve the sodium molybdate and thiourea; adjust the pH value to 1.5 with concentrated hydrochloric acid;

[0091] (2) Transfer the prepared solution to a reactor containing 50 ml of solvent; control the reaction temperature to 230°C and the reaction time to 16 hours; after the reaction is completed, take it out and naturally cool it to room temperature, centrifuge it with distilled water at a speed of 4000 rpm for 3-5 minutes, wash it with water centrifugation 4 times, and then centrifuge it with alcohol to obtain MoS2.

[0092] (3) The weighed MoS2 prepared by the hydrothermal method was placed in a drying oven at 60°C and dried for 12 hours before being taken out.

[0093] (4) Weigh 0.8 g of dried molybdenum disulfide and 2.02 g of ferric nitrate nonahydrate into a 500 ml conical flask, add 100 ml of deionized water, seal with plastic wrap, add a stirrer, and stir on a magnetic stirrer for 40 min; add 2.8 g of 25 wt % ammonia water dropwise, and continue stirring on the magnetic stirrer for 20 min;

[0094] (5) The stirred solution was placed in a microwave reaction box and reacted at 80°C and 1000W for 1 minute; the solution after the reaction was cooled naturally, washed with distilled water by centrifugation at 4000 rpm for 4 times, and then washed once with anhydrous ethanol, and then the resultant was placed in a drying oven at 60°C and dried for 12 hours;

[0095] (6) The dried product was placed in a crucible and calcined at 700°C in an air atmosphere for 0.5 h to obtain a Fe2O3 / Fe2(MoO4)3 nanocomposite material.

[0096] Comparative Example 1

[0097] A Fe2O3 / MoS2 nanocomposite material, the preparation method comprises the following steps:

[0098] (1) Dissolve 1.6 mmol of sodium molybdate (Na2MoO4; 98%) and 6.4 mmol of thiourea (H2NCS-NH2; 99%) in 40 mL of deionized water; continue stirring for 10 min to completely dissolve the sodium molybdate and thiourea; adjust the pH value to 2 with concentrated hydrochloric acid;

[0099] (2) The prepared solution was transferred to a reactor containing 50 ml of solvent; the reaction temperature was controlled to be 210°C and the reaction time was 12 hours; after the reaction was completed, the solution was taken out and naturally cooled to room temperature, centrifuged at 4000 rpm with distilled water for 3-5 minutes, washed with water four times by centrifugation, and then washed once with alcohol by centrifugation to obtain MoS2.

[0100] (3) The weighed MoS2 prepared by the hydrothermal method was placed in a drying oven at 60°C and dried for 12 hours before being taken out.

[0101] (4) Weigh 0.8 g of dried molybdenum disulfide and 2.02 g of ferric nitrate nonahydrate into a 100 ml conical flask, add 50 ml of deionized water, seal with plastic wrap, add a stirrer, and stir on a magnetic stirrer for 40 min; add 2.1 g of 25 wt % ammonia water dropwise, and continue stirring on the magnetic stirrer for 20 min;

[0102] (5) The stirred solution was placed in a microwave reaction box and reacted at 95°C and 400W for 3 minutes; the solution after the reaction was cooled naturally, and then washed with distilled water by centrifugation at 4000 rpm for 4 times, and then washed once with anhydrous ethanol, and then the resultant was placed in a drying oven at 60°C and dried for 12 hours;

[0103] (6) The dried product was placed in a crucible and calcined in a vacuum oven at 550°C for 2.5 h to obtain a Fe2O3 / MoS2 nanocomposite material.

[0104] Application Examples

[0105] Take the Fe2O3 / Fe2(MoO4)3 nanocomposite material prepared in Example 1 as an example to make a gas sensor. First, solder the ceramic tube to the base with solder, with four electrodes corresponding to four small pillars. And pass the resistor across the ceramic tube, and weld the two ends to the two small pillars in the middle. Secondly, pour a small amount of sample into a clean mortar, and add 1 to 2 drops of anhydrous ethanol. Use a grinding rod to fully grind the Fe2O3 / Fe2(MoO4)3 nanocomposite material sample prepared in Example 1, then use a clean brush to dip a small amount of the sample several times, and evenly apply it to the ceramic tube. Use the above method to make the gas sensors corresponding to the samples prepared in Examples 2-5 and Comparative Example 1 in turn.

[0106] Test Case

[0107] Figure 1 The electron microscope images of MoS2 prepared in step (2) of Example 1 and Example 6, (a) and (b) are the products prepared when the ratio of sodium molybdate to thiourea is 1:4 in Example 6, and (c) and (d) are the products when the ratio is 1:5. Figure 1 It can be seen that the Mo S2 product presents a granular structure, and when the thiourea content is high, that is, when the sodium molybdate:thiourea ratio is 1:5, the flaky structure is more obvious. It can be inferred that with the increase of the thiourea content in the solution, vertical tiny flaky structures appear on the surface of the granular structure. When the thiourea content in the solution decreases, the product morphology presents a flaky MoS2 structure standing on the surface of the agglomerate. When there is sufficient sulfur source in the hydrothermal reaction solution, it is more conducive to the growth of MoS2 nanosheets; in a sulfur-rich environment, it is conducive to the growth of MoS2.

[0108] Figure 2 This is the SEM image of the Fe2O3 / Fe2(MoO4)3 nanocomposite material prepared in Example 4; as can be seen from Figures (a) and (b), the Fe2O3 / Fe2(MoO4)3 nanocomposite material has undergone good compounding.

[0109] Gas-sensitive performance test: This is done by operating the gas-sensitive tester under the condition of a working voltage of 5 volts. At the same time, the temperature operating range of the tester can be controlled by adjusting the heating voltage. The load voltage at both ends of the test element can be changed by adjusting the load resistance, so as to achieve the purpose of testing the component at different temperatures. At different operating temperatures, the system conducted gas-sensitive performance tests on ethanol gas of different concentrations. The test temperatures were 160°C, 180°C, 200°C, 240°C, and 260°C respectively. The test concentrations of the target liquid were 1ppm, 3ppm, 5ppm, 10ppm, 25ppm, and 50ppm respectively.

[0110] Figure 3The XRD images of the Fe2O3 / Fe2(MoO4)3 nanocomposite prepared in Example 4 show that the sharp characteristic peaks are consistent with the standard spectrum of Fe2(MoO4)3 (b) JCPDS 83-1701 and (c) the standard spectrum of Fe2O3 JCPDS 03-0800, indicating that both Fe2O3 and Fe2(MoO4)3 exist and have good crystallinity. The main peaks of Fe2(MoO4)3 are (40-2)(21-4)(122), and the main peaks of Fe2O3 are (104)(116)(214).

[0111] Figure 4 The real-time sensitivity dynamic change curve of the Fe2O3 / Fe2(MoO4)3 nanocomposite prepared in Example 4 to different concentrations of ethanol gas, the test temperature is 200°C. Figure 4 It can be seen that the sensitivity of Fe2O3 / Fe2(MoO4)3 nanocomposite materials to ethanol gas increases with the increase of ethanol concentration. However, the sensitivity of Fe2O3 / MoS2 obtained by vacuum calcination in Comparative Example 1 to 50ppm ethanol gas at 200℃ is less than 5.

[0112] Figure 5 The responses of the Fe2O3 / Fe2(MoO4)3 nanocomposite prepared in Example 4 to different concentrations of ethanol gas at different temperatures. The sensitivity increases with the increase of ethanol gas concentration at each temperature. The sensitivity of the gas with the same concentration increases first and then decreases with the increase of temperature. The preferred test temperature is around 180-200°C, which is better than the previous reports that the best temperature is usually above 300°C, which has obvious advantages in low-temperature detection.

[0113] Figure 6 The response recovery time bar graph of the Fe2O3 / Fe2(MoO4)3 nanocomposite prepared in Example 4 at different temperatures shows that as the temperature increases, the response recovery time decreases and the response speed increases. The response recovery time is as short as 3s / 19s at 240°C and 5s / 30s at 220°C.

[0114] Figure 7 The selectivity of the Fe2O3 / Fe2(MoO4)3 nanocomposite material prepared in Example 4 to ethanol relative to other materials, wherein ethanol is 10 ppm and other gases are 100 ppm. It can be seen from the figure that the selectivity of the composite material to ethanol with a lower concentration is also better than that of other gases with a higher concentration.

[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a flower-like MoS2-induced Fe2O3 / Fe2(MoO4)3 nanocomposite material, characterized in that: The following steps are involved: (1) dissolving and mixing a molybdenum source and a sulfur source in solvent I, adjusting the pH, and obtaining molybdenum disulfide through a hydrothermal reaction; (2) dispersing and dissolving molybdenum disulfide and an iron source in solvent II, adding a precipitant, reacting under microwave-assisted conditions, and washing and drying the product; (3) calcining the dried product in air to obtain a Fe2O3 / Fe2(MoO4)3 nanocomposite material; The molybdenum source is sodium molybdate or ammonium molybdate; the sulfur source is thiourea; the solvent I is water or ethanol; The molar ratio of the molybdenum source to the sulfur source is 1:(3-5); the concentration of the molybdenum source in solvent I is 0.01-0.1 mmol / ml; The reagent used for adjusting the pH is concentrated hydrochloric acid, and the pH is adjusted to 1.5-2.5; the temperature of the hydrothermal reaction is 160-230°C, and the reaction time is 12-24h; The calcination temperature is 300-700° C. and the calcination time is 0.5-5 h.

2. The method for preparing the Fe2O3 / Fe2(MoO4)3 nanocomposite material according to claim 1, characterized in that: The iron source is ferric nitrate; the solvent II is water or ethanol; and the precipitant is urea or ammonia water.

3. The method for preparing the Fe2O3 / Fe2(MoO4)3 nanocomposite material according to claim 2, characterized in that: In the step (2), the ratio of molybdenum atoms to iron atoms in molybdenum disulfide and iron source is (8-3): (2-7); the molar ratio of the iron source to the precipitant is 1: (3-6); and the concentration of molybdenum disulfide in solvent II is 0.05-0.2 mmol / ml.

4. The method for preparing the Fe2O3 / Fe2(MoO4)3 nanocomposite material according to claim 3, characterized in that: The microwave-assisted conditions are: reaction temperature of 80°C-110°C, microwave power of 100-1000 W, and time of 1-20 min.

5. The Fe2O3 / Fe2(MoO4)3 nanocomposite material prepared by the method according to any one of claims 1 to 4.

6. Use of the Fe2O3 / Fe2(MoO4)3 nanocomposite material according to claim 5 in gas concentration detection.

Citation Information

Patent Citations

  • Molybdenum disulfide / magnesium hydroxide nano composite material as well as preparation method and application thereof

    CN106596651A

  • Gas sensor based on metal molybdate nano composite material and preparation method thereof

    CN109781800A